MALI : Staff Report for the 2000 Article IV Consultation, First Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Mali has made progress in reducing macroeconomic imbalances, improving the competitiveness of the economy, and alleviating economic distortions under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors commended this step, and stressed the need to maintain fiscal and monetary policies, and accelerate structural reforms. They noted that the Malian economy suffered from trade losses and difficulties in the cotton and electricity sectors, and urged to take necessary actions. They appreciated the authorities' commitment to the PRGF-supported program, and supported the request for waivers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet